Paths to a middle ground : the diplomacy of Natchez, Boukfouka, Nogales, and San Fernando de las Barrancas, 1791-1795 - Weeks, Charles A., 1937- (Tuscaloosa : University of Alabama Press, 2005)
Charles Weeks explores the diplomacy of Spanish colonial officials in New Orleans and Natchez in order to establish posts on the Mississippi River and Tombigbee rivers in the early 1790s. Another purpose of this diplomacy, urged by Indian leaders and embraced by Spanish officials, was the formation of a regional Indian confederation that would deter American expansion into Indian lands. Weeks shows how diplomatic relations were established and maintained in the Gulf South between Choctaw, Chickasaw, Creek, and Cherokee chiefs and their Spanish counterparts aided by traders who had become integr.
Part III: Documents1. Diary of Gayoso's Journey to Nogales, March 24April 23, 1791; 2. Franchimastab and Taboca to Gayoso, May 14, 1791; 3. Gayoso's Reply to Franchimastab and Taboca, May 28, 1791; 4. Diary of Minor's First Mission to the Choctaws May 30 to June 13, 1791; 5. Gayoso on Minor's Mission to the Choctaws, July 1, 1791; 6. Gayoso to Franchimastab, March 12, 1792; 7. Diary of Stephen Minor's Second Mission to the Ch.
Includes bibliographical references (pages 245-278) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Natchez Region (Miss.) -- Ethnic relations; Mobile Region (Ala.) -- Ethnic relations; Tombigbee River Region (Miss. and Ala.) -- Ethnic relations; Indians of North America -- Government relations -- 1789-1869.; Spaniards -- Mississippi -- Natchez -- History -- 18th century; Spaniards -- Louisiana -- New Orleans -- History -- 18th century; Colonial administrators -- Mississippi -- Natchez -- History -- 18th century; Colonial administrators -- Louisiana -- New Orleans -- History -- 18th century; Political culture -- Mississippi -- Natchez Region -- History -- 18th century -- Sources; Political culture -- Alabama -- Mobile Region -- History -- 18th century -- Sources; Peuples autochtones -- États-Unis -- Relations avec l'État -- 1789-1869.; Espagnols -- Mississippi -- Natchez -- Histoire -- 18e siècle.; Espagnols -- Louisiane -- La Nouvelle-Orléans -- Histoire -- 18e siècle.; Administrateurs coloniaux -- Mississippi -- Natchez -- Histoire -- 18e siècle.; Administrateurs coloniaux -- Louisiane -- La Nouvelle-Orléans -- Histoire -- 18e siècle.; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Ethnic Studies -- General; SOCIAL SCIENCE -- Minority Studies; Colonial administrators; Ethnic relations; Indians of North America -- Government relations; Political culture; Spaniards; Alabama -- Mobile Region; Louisiana -- New Orleans; Mississippi -- Natchez; Mississippi -- Natchez Region; Diplomatie; Natchez, Miss. -- Region; New Orleans, La; Spanier; Indianer; 1700-1869; History; Sources